Comparative study of in vitro anti-inflammatory activity of sweet potato (Ipomeae Batatas) - Ismail, Adibah (2018)
This research focused on investigating the anti-inflammatory activity of ipomeae batatas sp. that are commonly known for their goodness and benefit by consuming it. The study on the sweet potato that are one of the tuber family proving on the high content of nutrient in it which is beneficial to cure the inflammation. The different extracts of 95% ethanol and distilled water been used to extract the plant sample before the extract yield from the plant under study was completely screened for its intact protein using Bovine Serum Albumin (BSA) in the inhibition of albumin denaturation test. The in-vitro anti-inflammatory activity also involving the Chicken Red Blood Cells (CRBCS) for the membrane stabilization tests (heat-induced haemolysis test and hypotonicity-induced haemolysis test). The test showing the result of haemolysis that were occurred to the erythrocyte source in which the CRBCs can be conclude as going denatured by giving a higher Absorbance value since the light cannot penetrate through it when tested with spectrophotometer apparatus. The higher concentrations of ipomeae batatas definitely gave relatively more projecting anti-inflammatory in vitro activity against the lower concentration of plant extracts. The result of anti-inflammatory effects of the sample were then compared with those of Aspirin as a positive control.